Analysis of Volatile Organic Compounds in the Exhaled Breath of COVID-19 Patients - Tiar Oktavian Effendi; Iin Noor Chozin; Suryanti Dwi Pratiwi; Nanik Setijowati; Arinto Yudi Ponco Wardoyo (Jurnal Respirologi Indonesia, 2023)
Background: It has been more than 2 years since COVID-19’s first cases were reported in 2019. Rapid diagnosis of COVID-19 is necessary to prevent its spread. A sample for COVID-19 testing is collected by naso-oro-pharyngeal swab. This procedure is often uncomfortable and requires a trained examiner. Exhaled breath contains thousands of volatile organic compounds (VOC), which are likely to change during infection. This study aimed to analyze the difference in VOC in the exhaled breath between COVID-19 and healthy subjects.Methods: A cross-sectional study was carried out, recruiting 90 confirmed cases of COVID-19 and 42 healthy subjects. A sample of exhaled breath was collected by using a 500-mL airbag in both groups. The sample was analyzed using an arrayed sensor breath analyzer to quantify the concentration of CO2, C7H8, C6H14, CH2O, NH4, TVOC, NO2, PM1.0, CO, NH3 and Acetone.Results: The medians of CO2, NH4, TVOC, NO2, and acetone were significantly lower in COVID-19 patients compared to healthy subjects (respectively 607.3 vs 1175.1; 0.0 vs 1.05; 0.05 vs 146.6; 0.04 vs 1.55; 0.0 vs 0.23) while C7H8, CH2O, CO, and NH3 were significantly higher (respectively 0.92 vs 0.0; 0.55 vs 0.01; 0.24 vs 0.0; 1.99 vs 0.67; all with P-value of <0.05.). Furthermore, we found NH4, acetone, NH3, and CO were positively correlated with the severity of COVID-19, while CO2 and TVOC were negatively correlated.Conclusion: COVID-19 patients emit distinctive VOC profiles in comparison with healthy subjects, and this is related to the severity of the disease.